2015
DOI: 10.2174/1874916x01509010065
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Critical Thinking and Professional Reading with Literacy Bags

Abstract: Students enrolled in college courses are typically expected to read one or more textbooks per course. While the course text may be comprehensive, the author's approach may be narrow in focus, disregarding diverse perspectives on the subject. In addition, the limited genre presented in textbooks (i.e., nonfiction, expository) is not likely to encourage a desire for professional reading in students. To address these issues, two faculty members incorporated a Literacy Bag Project into their education courses at b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The use of reading bags may help to develop these skills among learners. The study by Greene and Serro (2015) focussed on motivating students to read through the use of literacy bags. The study found that there is a positive correlation between the usage of literacy bags on one hand and professional reading and critical reading on the other.…”
Section: Reading Bags As a Reading Promotion Strategymentioning
confidence: 99%
“…The use of reading bags may help to develop these skills among learners. The study by Greene and Serro (2015) focussed on motivating students to read through the use of literacy bags. The study found that there is a positive correlation between the usage of literacy bags on one hand and professional reading and critical reading on the other.…”
Section: Reading Bags As a Reading Promotion Strategymentioning
confidence: 99%